Analisis Pengaruh Profitabilitas Terhadap Harga Saham Pada Perusahaan Food And Beverages Yang Terdaftar Di Bei Tahun 2011-2014 - Sari, Aprilia Kartika (2016)
This study aimed to analyze the influence of the profitability of the company's share price at the Food and Beverages that are listed in the Indonesia Stock Exchange (BEI) in 2011-2014. In connection with the purpose of the study, the research hypothesis proposed that profitability ratios affect the company's share price at the Food and Beverages that are listed in the Indonesia Stock Exchange (BEI) in 2011-2014. This study uses a survey of secondary data with the population of Food and Beverages company listed on the Indonesia Stock Exchange (BEI) in 2011-2014. Criteria used to determine the sample with purposive sampling method this is a company whose shares are actively traded during the year 2011-2014, published financial statements. With this method obtained a sample of 8 companies. This study uses a measurement tool of corporate profitability is Return On Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS). The analytical method used is multiple regression model. Hypothesis testing is done by using t-test that tests the influence of independent variables are Return On Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earning Per Share (EPS) partially to the stock price, and test-F which examines the effect of profitability ratios together (simultaneously) on the dependent variable was the share price. The results using test Regression is concluded that the partial Return On Assets have a significant influence on stock prices, (2) Return on Equity has a significant influence on stock prices, (3) Net Profit Margin have a significant influence on stock prices and (4) Earning Per Share which have a significant influence on the price of shares in the company Food and Beverages which are listed in the Indonesia Stock Exchange (BEI) in 2011-2014.